(untitled) (Research, Society and Development, 2021)
This article discusses the constitutional principles that ensure the right to quality public and free education in Brazil. The objective is to analyze the Constitutional text revealing education as a social right and a public good. The problem that this research proposes to answer is: What are the guidelines of the Constitutional text for the effectiveness of education as a social right? The research is qualitative and the analyzes were based on a bibliographical study. From the set of analyzes carried out, we show that the right to education, as a fundamental right provided for in the 1988 Constitution and announced in the previous Constitutions, does not materialize, with the social quality expected for Brazilian education and with the democratic rule of law should guard.